2012
DOI: 10.4067/s0717-95022012000100032
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bifid Tongue and Ankyloglossia in South Indian Population with an Emphasis on its Embryogenesis

Abstract: SUMMARY:Disturbance in the organogenesis of tongue might lead to some malformations like tongue tie, bifid tongue and hairy tongue. Severe degrees of these anomalies may cause speech impairment or periodontal defects. The present study was done on patients of the southern coastal belt of India during the past two years, on gross tongue anomalies. The results of the present study reveal that occurrence of tongue tie is 0.2% and bifid tongue is 0.3% in the southern coastal population. Since great majority of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The absolute pathogenesis of ankyloglossia remains unknown. [ 3 ] While most cases of ankyloglossia are sporadic, mutations in the T-box transcription factor TBX22 may lead to heritable (X-linked) ankyloglossia with or without cleft lip, cleft palate and/or hypodontia. [ 8 ] Reports suggest that there is a genetic basis for the microvariation in the attachment of genioglossus muscle due to the mutations present in the TBX22 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute pathogenesis of ankyloglossia remains unknown. [ 3 ] While most cases of ankyloglossia are sporadic, mutations in the T-box transcription factor TBX22 may lead to heritable (X-linked) ankyloglossia with or without cleft lip, cleft palate and/or hypodontia. [ 8 ] Reports suggest that there is a genetic basis for the microvariation in the attachment of genioglossus muscle due to the mutations present in the TBX22 gene.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Among South Indian population, the occurrence of tongue tie is relatively rare with an incidence of 0.2%. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed excess functional promoter haplotype in cleft palate patients with ankyloglossia than without ankyloglossia, indicating that ankyloglossia is a useful, but not exclusive, diagnostic feature to identify the X-linked patients (Pauws et al, 2009b). However, in the south Indian population, the occurrence of ankyloglossia is relatively rare, with an incidence of 0.2% (Rai et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Partial ankyloglossia and median grooved tongue could be congenital defects linked to breast feeding difficulties of those patients. [22][23][24] All studied PWS patients had infantile hypotonia and at least two PWS facial features during neonatal and early childhood period, while sixteen patients (94.1%) had feeding difficulties. At the time of examination all studied patients presented with hypotonia.…”
Section: Resultsmentioning
confidence: 99%